Improving the english teaching-learning process in the seventh grade at Santa María de la Esperanza elementary school with the use of flashcards - Calle León, Patricio; Chuchuca Chérrez, Pablo
This project explores the importance of visual material in an English class. We have focused our project on the use of flashcards in activities that the English teachers can make use of them in the teaching-learning process not only to motivate learners to participate but also to introduce new vocabulary, practice pronunciation and play active games that the students enjoy in each English class. Also, this work suggests some activities that involve the use of the 150 flashcards, which we elaborated, based on Piaget´s Cognitive Development Theory and Gardener´s Multiple Intelligences Theory. Piaget´s theory reminds us that the children´s thinking process develops through four stages in which they, first, make use of senses and motor capabilities. Then they use symbols to represent objects, and later think logically and abstractly to solve complex problems. Moreover, Gardener suggests that teachers can present their lessons in a wide variety of ways using music, cooperative learning, art activities, role playing, multimedia, field trips, inner reflection, and many more because there are different kinds of learners in an English class. Our goal through this work is to help English teachers, and especially the teacher of the seventh grade at Santa Maria de la Esperanza Elementary School to enhance the teaching-learning process with the use of some flashcard activities that a teacher easily can use in a course